Soil macrofauna in agroecosystems of Coffea arabica L., in Tepec-Xomolth, Nicaragua - Morán Centeno, Juan Carlos (2024)
Introduction. The coffee plant is an item of great importance worldwide, as it has a direct impact on the economy of the countries. In Nicaragua, it represents 25 % of exports. The coffee plant production agroecosystem is made up of components that are found above and below the soil surface. Objective. To estimate the populations of soil macrofauna in productive coffee plantation agroecosystems and their relationship with soil fertility and management practices. Materials and methods. The research was carried out from May to August 2023 in fourteen coffee plantation production systems in the Tepec-Xomolth La Patasta nature reserve. Soil monoliths measuring 25 × 25 × 20 cm were extracted, and three transects were established in each system, separated by 50 m. Specimens collected were identified at the family level. The data were analyzed using descriptive statistics, generalized linear models, hypothesis tests, and diversity indices. Results. Significant statistical differences (p<0.5) were found for rural communities and practices. Soil fertility varied according to the altitude of the farms, with abundant macrofauna in the Nueva Esperanza community (20,672 individuals) and shade management (23,632 individuals). Fifteen orders and 38 families were identified, with the insect class and the trophic group of predators predominating. Diversity was high and stable, a result of the management practices employed by the producers. Conclusions. Taxonomic richness and abundance of macrofauna were similar in the evaluated systems, specifically in the orders Haplotaxida, Coleoptera, Hymenoptera, and Isopoda, where detritivores, omnivores and predators stand out. The study revealed that crop management directly affects soil diversity, indicating that the soils are minimally disturbed and there is ecological balance.